Pengaruh Flash Sale, Customer Review, Dan Harga Terhadap Keputusan Pembelian Produk Wardah Di Shopee (Studi Kasus Mahasiswa FEB Prodi Manajemen Angkatan 2020 Universitas Bhayangkara Jakarta Raya) - Helmi Dayanti; Andrian Andrian; Haryudi Anas (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In this study using quantitative research methods where the sampling technique used is simple random sampling with the calculation of the slovin formula to obtain samples in this study. The sample size used in this study was 135 respondents and focused on Wardah consumers who are also students of Bhayangkara University Jakarta Raya. The results of this study indicate that there are variables that influence each other, as briefly explained below: 1) Flash sales partially have a positive and significant effect on purchasing decisions. 2) Cutomer review partially has a positive and significant effect on purchasing decisions. 3) Price partially has a positive and significant effect on purchasing decisions. 4) Flash sale, customer review, and price simultaneously have a positive and significant effect on purchasing decisions.